2022
DOI: 10.1101/2022.03.04.482636
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immunogenicity of an Ad26-based SARS-CoV-2 Omicron Vaccine in Naïve Mice and SARS-CoV-2 Spike Pre-immune Hamsters

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) Omicron variant sparked concern due to its fast spread and the unprecedented number of mutations in the spike protein that enables it to partially evade spike-based COVID-19 vaccine-induced humoral immunity. In anticipation of a potential need for an Omicron spike-based vaccine, we generated an Ad26 vector encoding an Omicron (BA.1) spike protein (Ad26.COV2.S.529). Ad26.COV2.S.529 encodes for a prefusion stabilized spike protein, similar to the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Some small-scale animal studies found Omicron-specific mRNA-based boosters offer little advantage over the original vaccines in rhesus macaques and mice that were previously immunized with 2 doses of the original vaccine [ 239 , 240 ]. Nonetheless, boosting with Omicron-specific mRNA (mRNA-1273.529) and Ad26 viral vector (Ad26.COV2.S.529) vaccine candidates both induced stronger Omicron-neutralizing responses in pre-immunized rodents when compared to boosting with the original vaccine [ 240 , 241 ]. Additionally, the timing of boosting should be optimized, as preexisting immunity may compromise the effect of the booster dose [ 130 , 242 ].…”
Section: Next-generation Vaccinementioning
confidence: 99%
See 1 more Smart Citation
“…Some small-scale animal studies found Omicron-specific mRNA-based boosters offer little advantage over the original vaccines in rhesus macaques and mice that were previously immunized with 2 doses of the original vaccine [ 239 , 240 ]. Nonetheless, boosting with Omicron-specific mRNA (mRNA-1273.529) and Ad26 viral vector (Ad26.COV2.S.529) vaccine candidates both induced stronger Omicron-neutralizing responses in pre-immunized rodents when compared to boosting with the original vaccine [ 240 , 241 ]. Additionally, the timing of boosting should be optimized, as preexisting immunity may compromise the effect of the booster dose [ 130 , 242 ].…”
Section: Next-generation Vaccinementioning
confidence: 99%
“…Additionally, the timing of boosting should be optimized, as preexisting immunity may compromise the effect of the booster dose [ 130 , 242 ]. Notably, animal studies also found Omicron-specific vaccines induced potent antibodies and immunity against Omicron but not the ancestral strain in vaccine-naive mice and Syrian hamsters [ 241 243 ]. A serological study of vaccine-naive individuals infected with Omicron also showed that their sera contain nAbs against Omicron but not the other variants [ 244 ].…”
Section: Next-generation Vaccinementioning
confidence: 99%